From poverty to history maker : an autobiography - Holmes, R. (Robert A.), 1943- (University Press of America, 2014)
This book describes how Robert "Bob" Holmes, a former juvenile delinquent, rose from humble beginnings in West Virginia and Harlem, New York to become an influential voice in academics and politics. This book provides an analysis of four decades of Georgia legislative politics from the perspective of a political insider.